CONSUMPTION PATTERN OF FOODS HIGH IN FAT, SALT, AND SUGAR IN THE ADULT POPULATION OF URBAN VADODARA - *S. DHRUV, U. IYER, U. GOHIL and A BAHUGUNA (The Journal of Research ANGRAU, 2022)
Conventionally known for malnutrition, Indians now frequently report obesity and itsconsequences. Diets have varied from a traditional patternto foods high in fat, salt, and sugar (HFSS).This cross-sectional study was carried out on adults of urban Vadodara during 2017.Data concerningthe socio-economic status, medical history, anthropometry, physical activity, dietary pattern, foodpurchasing pattern, quantitative food frequency, and three days 24-hour dietary recall were obtained.Anthropometric measurements indicated that 18% of subjects were overweight, 40% obese and 90%were abdominally obese. The majority of the respondents were physically inactive. Respondentsreported strong family history of diabetes, hypertension, and hyperlipidemia. Meal skipping waspersistent amongthe overweight and obese people. Almost all the respondents consumedhigh in fat,salt and sugar (HFSS) foods with wavering frequency with the predominant impetus being taste. Mostfrequently consumed HFSS foods were wafers, puffs, samosa, ice cream, papad, andsoft drink. The3 days 24-hour dietary recall conceded that energy intake escalated by 203 kcal during weekendscompared to weekdays. The mean per capita intake of oil, salt, and sugar was 56.15g, 12.69g, and32.05g, respectively.Consumption of HFSS foods was particularly exorbitant among overweight andobese subjects.